Reading Old Testament narrative as Christian scripture - Earl, Douglas S. (Winona Lake, IN Eisenbrauns, 2017)
Douglas Earl sets out a fresh perspective on understanding what is involved in reading Old Testament narrative as Christian Scripture. Earl considers various narratives as examples that model different interpretive challenges in the form of exegetical, ethical, historical, metaphysical, and theological difficulties. Using these examples, the significance of interpretive approaches focused on authorial intention, history of composition, canonical context, reception history, and reading context are considered in conjunction with spiritual, literary, structuralist, existential, historical-critical, and ethical-critical approaches. Christian interpretation of Scripture as Scripture is shown to be an inherently ad hoc task, understood as a rule-governed practice in Wittgenstein's sense: an established goal-directed activity for which no method, hermeneutical principle, or critical perspective discovers "meaning" or generates good interpretation. Good interpretation involves exploration of various construals of the "world of the text" using "hermeneutics of tradition" and "critique of ideology" (Ricoeur). The interpreter's task is to discern faithful readings and develop their significance in a given intellectual or cultural context. The interpretation of Scripture and its appropriation is seen to involve wisdom in forming judgments on a case-by-case basis, learned through examples and experience, on what constitutes good interpretation and use. Earl shows how traditional hermeneutics and contemporary critical resources suggest that history, ethics, and theology can rarely be "read off" Old Testament narrative, but also how Christians can appropriate ethically and historically problematic books such as Joshua, faithfully adopt a "minimalist" approach to 1-2 Samuel, and embrace a Trinitarian reading of Genesis 1
Keywords: Bible; Electronic books